DIALOGIC PROCESSES THAT COEXIST IN THE UNIVERSITY ETHOS OF THE DOCTORATE IN EDUCATION OF THE "RAFAEL MARÍA BARALT" NATIONAL EXPERIMENTAL UNIVERSITY - Rodríguez , Erwin (Revista Arbitrada Formación Gerencial, 2024)
The purpose of this essay is to describe and interpret the dialogical processes of the educational fact that emerge from the Doctorate in Education of the National University "Rafael María Baralt", the applied methodology is the phenomenological hermeneutic with a data collection technique, as well as its meanings. This allowed both teachers and students to explore their ethical and moral responsibilities. On the other hand, it is important to encourage the university to give qualitative research in the socio-political, socio-critical, socio-semiotic and educational environment as part of the Unermbista culture, under well-defined aspects of social consciousness and social fitness.